(untitled) (Journal of Educational Sciences, 2016)
The article describes the author’s experience in the development and testing of technology training sessions at the University, allowing the design of trajectory of vocational and personal development of the student in the research of the educational environment. The author provides a definition of individual student’s development path «, is characterized by the design of individual trajectory of development student research in the educational environment, showcased the achievements for the tutors theory and practice of design trajectories of individual student research in the educational environment,» technology developed by the author are the competence of course, Reality-Education, technology, competence-oriented descriptive praise.